Aqueous history of Mars as inferred from landed mission measurements of rocks, soils, and water ice. Issue 9 (23rd September 2016) - Arvidson, Raymond E.
Abstract: The missions that have operated on the surface of Mars acquired data that complement observations acquired from orbit and provide information that would not have been acquired without surface measurements. Data from the Viking Landers demonstrated that soils have basaltic compositions, containing minor amounts of salts and one or more strong oxidants. Pathfinder with its rover confirmed that the distal portion of Ares Vallis is the site of flood‐deposited boulders. Spirit found evidence for hydrothermal deposits surrounding the Home Plate volcanoclastic feature. Opportunity discovered that the hematite signature on Meridiani Planum as seen from orbit is due to hematitic concretions concentrated on the surface as winds eroded sulfate‐rich sandstones that dominate the Burns formation. The sandstones originated as playa muds that were subsequently reworked by wind and rising groundwater. Opportunity also found evidence on the rim of the Noachian Endurance Crater for smectites, with extensive leaching along fractures. Curiosity acquired data at the base of Mount Sharp in Gale Crater that allows reconstruction of a sustained fluvial‐deltaic‐lacustrine system prograding into the crater. Smectites and low concentrations of chlorinated hydrocarbons have been identified in the lacustrine deposits. Phoenix, landing above the Arctic Circle, found icy soils, along with low concentrations of perchlorate salt. Perchlorate is considered to be a strong candidate for the oxidant found by the Viking Landers. It is also a freezing point depressant and may play a role in allowing brines to exist at and beneath the surface in more modern periods of time on Mars. Key Point: Landed mission data indicate sustained surface and subsurface waters in Martian past